2020
DOI: 10.1002/cem.3289
|View full text |Cite
|
Sign up to set email alerts
|

Model selection techniques for sparse weight‐based principal component analysis

Abstract: Many studies make use of multiple types of data that are collected for the same set of samples, resulting in so‐called multiblock data (e.g., multiomics studies). A popular analysis framework is sparse principal component analysis (PCA) of the concatenated data. The sparseness in the component weights of these models is usually induced by penalties. A crucial factor in the use of such penalized methods is a proper tuning of the regularization parameters used to give more or less weight to the penalties. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Estimating a smaller number of non-zero weights did not decrease the amount of explained variance, compared to the model found above with 107 non-zero weights per component. This is in line with previous findings in the literature that showed that high levels of sparsity in weights can still explain large amount of variance (de Schipper & Van Deun, 2021 ). In contrast, USLPCA-svd and USLPCA-multi resulted in 6.5% and 7.4%.…”
Section: Appendix A: Sparse Weights Indeterminacy Problemsupporting
confidence: 93%
“…Estimating a smaller number of non-zero weights did not decrease the amount of explained variance, compared to the model found above with 107 non-zero weights per component. This is in line with previous findings in the literature that showed that high levels of sparsity in weights can still explain large amount of variance (de Schipper & Van Deun, 2021 ). In contrast, USLPCA-svd and USLPCA-multi resulted in 6.5% and 7.4%.…”
Section: Appendix A: Sparse Weights Indeterminacy Problemsupporting
confidence: 93%